Handy Literacy Practice Using Instagram Among Twelve Graders: Pragmastylistic Viewpoint - Indah Miftakhul Jannah; Lies Amin Lestari; Ahmad Munir; Slamet Setyawan (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2022)
Abstract. The student’s communication in writing has a different style. It is interesting to be studied since it relate with literacy practice especially in using technology.  Thus, this current study was conducted to explore the figurative language and discourse goals made by students in their Instagram posts. This study also describes the student’s strategy in using figurative language to create an Instagram post as a literacy practice. The study use Qualitative method with documentation and interview as the instruments. Seventy-one student’s Instagram posts were analyzed, and 5 of the students who posted them interviewed. The finding is interesting because only little student who used figurative language and has a clearly discourse goal in their Instagram post. The data shows that only 16,9% of students used figurative language in Instagram posts. Only found 3 figurative languages are used by the student, 7 sentences classified as Metaphor, 3 sentences are Simile and Personification. Metaphor is one of the types of figurative language mostly found in the Instagram post. The result also shows that there are 5 discourse goals found in this study, they are being humorous, protecting the self, comparing similarities, showing positive emotion, and guiding another action. Comparing similarities is the majority of discourse goals of students in their Instagram posts. Although student has limited writing style in using figurative language for creating an Instagram post, the student can create an appropriate picture and caption to share the idea to communicate using Instagram.Keywords: Figurative Language, Discourse Goal, Literacy Practice